2023
DOI: 10.3390/brainsci13020329
|View full text |Cite
|
Sign up to set email alerts
|

Embryoid Body Cells from Human Embryonic Stem Cells Overexpressing Dopaminergic Transcription Factors Survive and Initiate Neurogenesis via Neural Rosettes in the Substantia Nigra

Abstract: Transplantation of immature dopaminergic neurons or neural precursors derived from embryonic stem cells (ESCs) into the substantia nigra pars compacta (SNpc) is a potential therapeutic approach for functional restitution of the nigrostriatal pathway in Parkinson’s disease (PD). However, further studies are needed to understand the effects of the local microenvironment on the transplanted cells to improve survival and specific differentiation in situ. We have previously reported that the adult SNpc sustains a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…We previously demonstrated that the 6-OHDA-lesioned SNpc favors the Th+ fate of grafted embryoid body cells (EBCs) derived from mouse ESCs and human EBCs overexpressing dopaminergic transcription factors [ 39 , 40 ]. To assess the Th+ lineage maturation potential of 3X SNCA and SNCA 4KO floor-plate progenitors in the SNpc, we examined the Th expression compared to the wild-type line.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that the 6-OHDA-lesioned SNpc favors the Th+ fate of grafted embryoid body cells (EBCs) derived from mouse ESCs and human EBCs overexpressing dopaminergic transcription factors [ 39 , 40 ]. To assess the Th+ lineage maturation potential of 3X SNCA and SNCA 4KO floor-plate progenitors in the SNpc, we examined the Th expression compared to the wild-type line.…”
Section: Resultsmentioning
confidence: 99%
“…These results strongly suggest the feasibility of the survival and effective differentiation of dopaminergic neurons derived from dopaminergic progenitor cells in the SNpc. Our data demonstrate that the intact rat SNpc is a permissive neurogenic environment for neuronal development [ 38 , 39 , 40 ]. Yet, it does not inherently promote the mesencephalic dopaminergic phenotype without the overexpression of key dopaminergic transcription factors like Lmx1a [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations